DNA Cleavage, Cytotoxic Activities, and Antimicrobial Studies of Ternary Copper(II) Complexes of Isoxazole Schiff Base and Heterocyclic Compounds - Vijay Kumar Chityala; K. Sathish Kumar; Ramesh Macha; Parthasarathy Tigulla; Shivaraj (Bioinorganic Chemistry and Applications)
Novel mixed ligand bivalent copper complexes [Cu. L. A. ClO4] and [Cu. L. A] where “L” is Schiff bases, namely 2-((3,4-dimethylisoxazol-5-ylimino)methyl)-4-bromophenol (DMIIMBP)/2-((3,4-dimethylisoxazol-5-ylimino)methyl)-4-chlorophenol (DMIIMCP), and “A” is heterocyclic compound, such as 1,10-phenanthroline (phen)/2,21-bipyridyl (bipy)/8-hydroxyquinoline (oxine)/5-chloro-8-hydroxyquinoline (5-Cl-oxine), have been synthesized. These complexes have been characterized by IR, UV-Vis, ESR, elemental analysis, magnetic moments, TG, and DTA. On the basis of spectral studies and analytical data, five-coordinated square pyramidal/four-coordinated square planar geometry is assigned to all complexes. The ligands and their ternary complexes with Cu(II) have been screened for antimicrobial activity against bacteria and fungi by paper disc method. The antimicrobial studies of Schiff bases and their metal complexes showed significant activity and further it is observed that the metal complexes showed more activity than corresponding Schiff bases. In vitro antitumor activity of Cu(II) complexes was assayed against human cervical carcinoma (HeLa) cancer cells and it was observed that few complexes exhibit good antitumor activity on HeLa cell lines. The DNA cleavage studies have also been carried out on pBR 322 and it is observed that these Cu(II) complexes are capable of cleaving supercoiled plasmid DNA in the presence of H2O2 and UV light.